Rapid non-genomic inhibition of ATP-induced Cl(−) secretion by dexamethasone in human bronchial epithelium - Urbach, V (Blackwell Science Inc, 2002)
A non-genomic antisecretory role for dexamethasone at low concentrations (0.1 nm to1 μm) is described in monolayers of human bronchial epithelial cells in primary culture and in a continuous cell line (16HBE14o- cells). Dexamethasone produced a rapid decrease of [Ca(2+)](i) (measured with fura-2 spectrofluorescence) to a new steady-state concentration. After 15 min exposure to dexamethasone (1 nm), [Ca(2+)](i) was reduced by 32 ± 11 nm (n = 7, P < 0.0001) from a basal value of 213 ± 36 nm (n = 7). We have shown previously that aldosterone (1 nm) also produces a rapid fall in [Ca(2+)](i); however, after the decrease in [Ca(2+)](i) induced by dexamethasone, subsequent addition of aldosterone did not produced any further lowering of [Ca(2+)](i). The rapid response to dexamethasone was insensitive to pretreatment with cycloheximide and unaffected by the glucocorticoid type II and mineralocorticoid receptor antagonists RU486 and spironolactone, respectively. The rapid [Ca(2+)](i) decrease induced by dexamethasone was inhibited by the Ca(2+)-ATPase pump inhibitor thapsigargin (1 μm), the adenylate cyclase inhibitor MDL hydrochloride (500 μm) and the protein kinase A inhibitor Rp-adenosine 3′,5′-cyclic monophosphorothioate (200 μm), but was not affected by the protein kinase C inhibitor, chelerythrine chloride (0.1 μm). Treatment of 16HBE14o- cell monolayers with dexamethasone (1 nm) inhibited the large and transient [Ca(2+)](i) increase induced by apical exposure to ATP (10(−4)m). Dexamethasone (1 nm) also reduced by 30 % the Ca(2+)-dependant Cl(−) secretion induced by apical exposure to ATP (measured as the Cl(−)-sensitive short-circuit current across monolayers mounted in Ussing chambers). Our results demonstrate, for the first time, that dexamethasone at low concentrations inhibits Cl(−) secretion in human bronchial epithelial cells. The rapid inhibition of Cl(−) secretion induced by the synthetic glucocorticoid is associated with a rapid decrease in [Ca(2+)](i) via a non-genomic mechanism that does not involve the classical glucocorticoid or mineralocorticoid receptor. Rather, it is a result of rapid non-genomic stimulation of thapsigargin-sensitive Ca(2+)-ATPase, via adenylate cyclase and protein kinase A signalling.